Challenges and research priorities to understand interactions between climate, ice sheets and global mean sea level during past interglacials. (1st September 2019) - Capron, Emilie; Rovere, Alessio; Austermann, Jacqueline; Axford, Yarrow; Barlow, Natasha L.M.; Carlson, Anders E.; de Vernal, Anne; Dutton, Andrea; Kopp, Robert E.; McManus, Jerry F.; Menviel, Laurie; Otto-Bliesner, Bette L.; et al.
Abstract: Quaternary interglacials provide key observations of the Earth system's responses to orbital and greenhouse gas forcing. They also inform on the capabilities of Earth system models, used for projecting the polar ice-sheet and sea-level responses to a regional warmth comparable to that expected by 2100 C.E. However, a number of uncertainties remain regarding the processes and feedbacks linking climate, ice-sheet and sea-level changes during past warm intervals. Here, we delineate the major research questions that need to be resolved and future research directions that should be taken by the paleoclimate, sea-level and ice-sheet research communities in order to increase confidence in the use of past interglacial climate, ice-sheet and sea-level reconstructions to constrain future predictions. These questions were formulated during a joint workshop held by the PAGES-INQUA PALSEA (PALeo constraints on SEA level rise) and the PAGES-PMIP QUIGS (QUaternary InterGlacialS) Working Groups in September 2018.